Conflict and Catholic social ethics: an interdisciplinary approach - Ott, Taylor J. (Routledge new critical thinking in religion, theology and biblical studies, 2025)
"This book focuses on the question of how to understand conflict and its place in Catholic and Christian social ethics. The author examines Catholic social teaching (CST) for its explicit mentions of conflict or contention, and analyzes the way that CST addresses the subjects of peace, labor, and environment. While CST offers precedent to think about conflict within the frame of Catholic ethics, its lack of explicit engagement remains a major obstacle to a full, rich, and concrete understanding of the fabric of society and the work of social justice. Any social ethic that is not informed by the presence of conflict misses a major dynamic in society, and therefore leads to ethical judgements that are at best inadequate, and at worst, actively harmful. Building upon the insight of respected thinkers within Catholic social thought, this study is based on an interdisciplinary method that engages sociology, political theory, postcolonial theory, and intersectional feminist ethics. The book will be of particular interest to theological ethicists and those who work with modern Catholic social teaching"--